(untitled) (International Journal of Built Environment and Sustainability, 2022)
Homestays refers to locations for the tourist attraction of sites that may be on beaches, mountains, lakes or homes, typically places of scenic beauty. Three aspects: operation, amenities and attractions are the main attributes of homestays. Closeness to local culture further enhances guest satisfaction, helping to retain the rich heritage of the region. Domestic resources and natural habitats are used to promote sustainable tourism. Therefore, the promotion of tourism depends primarily on active private sector involvement and societies playing a beneficial role. The past researches on homestays lack the various attributes that plays a significant role towards guest experience in homestay and how they create a significant impact on their overall satisfaction.This paper focuses on understanding the concept of Homestays in Tourism and the various factors affecting its overall satisfaction through guest experience during holiday homestays. A field survey was conducted along the coastal belts to understand the guest preference, their cultural experience and their satisfaction level during the duration of their visit. It also analyzes the relationship and impact between overall tourist satisfaction and residence quality of homestays. This helps all stakeholders create sustainable tourism strategies, including host tourism. The outcome of the research is to explore the perception of tourist satisfaction with India during vacation homestays. Recommendations were made for further enhancement of Homestays’ based on the findings.